Stem Cells and Cancer Stem Cells, Volume 5 Therapeutic Applications in Disease and Injury - Hayat, M.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
The fifth volume in the essential series on stem cell biology provides a detailed explanation of the mechanisms of self-renewing cancer stem cells, as well as their ability to generate the heterogeneous lineages of cancer cells that comprise tumors. It explores the unique resistance of cancer stem cells to conventional chemotherapy techniques able to kill a tumor$1 (Bs constituent cells. The contents also include a discussion of the myriad applications of a selection of stem cells in treating disease and tissue injury. The cells singled out include human mesenchymal, arterial, neural, cardiac, dental, limbal, and hematopoietic stem cells. The therapeutic utility of uniquely adaptable human embryonic stem cells, able to generate any human cell type, is explored in depth. The volume looks at their uses in tissue engineering and regenerative medicine, as well as pharmacological, toxicological, and cell differentiation research. It also sheds light on the processes by which embryonic stem cells begin to differentiate by aggregating into more complex embryoid bodies. With additional material on targeting self-renewal pathways in cancer stem cells, the use of mesenchymal stem cells in treating ischemic brain injury, and the phenomenon of neural stem cell proliferation around traumatic brain injuries, this richly diverse and hugely informative book is a powerful tool for deepening professional expertise among researchers and practitioners in this field.s
Cancer Stem Cells -- 1 Signaling Pathways In Cancer Stem Cells Therapeutic Implications -- 2 Inhibition Of Telomerase With Imetelstat Causes Depletion Of Cancer Stem Cells -- 3 Targeting Self-Renewal Pathways In Cancer Stem Cells -- 4 Detection Of Cancer Stem Cells Using Ac133 Antibody -- Tissue Injury -- 5 Peripheral Nerve Regeneration After Traumatic Injury And Stem Cell Therapy -- 6 Neural Stem Cell Proliferation Surrounding The Area Of Traumatic Brain Injury Role Of Exercise Therapy -- 7 Mesenchymal Stem Cell Treatment For Ischemic Brain Injury -- 8 Role Of Neuropeptide Y On The Maintenance Of Self- Renewal And Proliferation Of Human Embryonic Stem Cells -- Cardiovascular Applications -- 9 Differentiation Of Human Adipose-Derived Stem Cells Into Cardiomyocytes -- 10 Cellular Cardiomyoplasty Arterial Cells-Stem Cells Transplantation -- 11 Cardiac Stem Cells Derived From Epithelial-Mesenchymal Transition Of The Epicardial Cells Role In Heart Regeneration (Method) -- 12 Allogenic Mesenchymal Stem Cells In Experimental Ischaemic Stroke Translation To The Clinic?- Bone Diseases -- 13 Bone Reconstruction Utilizing Mesenchymal Stem Cell Sheets For Cell Delivery -- 14 Dental Implants Application Using Tissue Engineering Technology -- 15 Dental Stem Cells Regeneration Of Dentin Upon Tooth Injury -- 16 Scaffolds For Human Dental Stem Cells To Regenerate Cementum -- Eye Disorders -- 17 Eye Disorders Caused By Limbal Stem Cell Deficiency -- Viral Applications -- 18 Current Diagnosis And Treatment Strategy For Chronic Active Epstein-Barr Virus Infection -- 19 Reprogramming Of Human Fibroblasts Into Pluripotent Cells Role Of Lentiviral Mediated Transcription Factors -- 20 Patients With Human Immunodeficiency Virus Hematopoeitic Stem Cell Transplantation -- 21 Cytomegalovirus Infection After Hematopoietic Stem Cell Transplantation In Children -- Neural Cells -- 22 Monolayer Culture Condition For Mouse Embryonic Stem Cells Differentiation Into Neural Crest Cells (Method) -- 23 Pro-Angiogenic Properties Of The Neural Stem/Progenitor Cells -- 24 Neural Differentiation Of Embryonic Stem Cells Role Of Fgfs -- 25 Neural Stem Cells Differentiated From Embryonic Stem Cells Proteomic Identification Of Expressed Genes -- Tissue Engineering -- 26 Chondrogenesis From Human Mesenchymal Stem Cells Role Of Culture Conditions -- 27 Urethral Tissue Engineering Using Urine-Derived Stem Cells -- 28 Chondrocytes And Mesenchymal Stem Cells In Cartilage Tissue Engineering And In The Regenerative Therapy Of Joint Diseases.
Keywords: Medicine; Oncology; Gene expression; Medical laboratories; Neurosciences; Pathology; Biomedicine; Cancer Research; Gene Expression; Laboratory Medicine; Neurosciences; Oncology; Pathology